Lithuanian basic school students achievements in mathematics - Dudaitė, Jolita (Lietuvos matematikos rinkinys, 2004)
Lithuanian National Student Achievement Studies have been carried out for already two years. In 2002 Grade 6 students were tested, and in 2003, Grade 4 and Grade 8 students. Some of the main findings from their results in Mathematics are presented in the article, illustrated by several simple examples. It is noticed that a big number of students have problems in relation to understanding the fundamental concepts and having main skills in all the content areas of Mathematics.